Czech Republic : 2005 Article IV Consultation-Staff Report and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2005 Article IV Consultation highlights that recent accession to the European Union and gains in growth performance reinforced the Czech Republic's position as one of the most open and developed economies among the new member states. Thanks to substantial foreign direct investment, its manufacturing sector is closely integrated into cross-border production networks, and foreign-owned firms now account for most of industrial exports. Banking sector indicators are positive, and bank lending-led by credit to households-continue to rebound. Past restructuring and improved risk management have also strengthened banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet